Near-Surface Characterization Using Integrated MASW and Seismic Refraction Tomography: A Scoping Review - Syamsuddin Syamsuddin; Kormil Saputra; Olfi Destika; Winny Anindya Nadi; Zaura Intan Zaraoda (Darul Yasin Al Sys, 2026)
Subsurface characterization is essential in engineering geology, geotechnical engineering, hydrogeology, and disaster mitigation because subsurface material conditions influence soil stability, seismic response, weak-zone identification, and infrastructure suitability. This study aims to map the development, characteristics, advantages, limitations, and research gaps related to the use of Multichannel Analysis of Surface Waves (MASW) and Seismic Refraction Tomography (SRT) in subsurface analysis. A scoping review approach was employed following PRISMA-ScR guidelines. Literature was obtained from ProQuest, ScienceDirect, and SpringerLink for the 2012–2026 publication period. Of the 852 articles identified, 23 studies met the inclusion criteria and were analyzed further. The findings show that MASW is effective for identifying variations in shear wave velocity (Vs), Vs30, soft layers, soil stiffness, and dynamic site response, whereas SRT is more effective for mapping compression wave velocity (Vp), layer thickness, bedrock boundaries, and lithological contrasts. The integration of MASW and SRT provides more robust subsurface interpretation, particularly in landslide, karst, landfill, sabkha, hydrogeological, and post-earthquake areas. However, several important research gaps remain, including the lack of standardized integration protocols, limited investigation depth, minimal validation with borehole data, ambiguity in integration with Horizontal-to-Vertical Spectral Ratio methods, insufficient systematic modeling of water content, and the limited number of studies in tropical, swamp, and peat environments. This study contributes to near-surface geophysical research by synthesizing current evidence on MASW and SRT integration and identifying methodological priorities for improving subsurface characterization in complex geological settings.